ANALISIS METODE PENGAKUAN PENDAPATAN PADA PT. CAHAYA SURYA PERSADA DI MAKASSAR - Rostiaty Yunus (AkMen JURNAL ILMIAH, 2014)
This study aims to determine how the recognition that applied by the company with a statement of Financial Accounting Standard 23 In. Light Surya Persada In Makassar. the method used is descriptive method in a way that suggests Comparative recognition in the company and comparing with Financial Accounting Standards (IFRSs) No. 23. Results showed that recognition pendapaatan at. Surya Persada Light Special and contract income, using the amount of the contract price is recognized or approved by the employer as income (gross concep) This is in accordance with the provisions outlined SAK.